A hospital based analytical study of ovarian neoplasms among adolescent girls with clinicopathological correlation - V., Nayanashree; Banapurmath, Sudha T. R.; Paul, Nancy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: To study the prevalence of different histopathological types of ovarian tumors and their management, and clinic pathological correlation among girls of age 8-19 years. Methods: A retrospective analytical study conducted among girls of age 8-19 years, diagnosed with ovarian tumour at Sri Chamarajendra Hospital from 2016-2022. Demographic data, age of presentation, size of tumour, histopathological type of tumor, type of surgery performed were analysed and correlation between radiological and histopathological findings were noted. Results: Among 42 girls aged between 8-19 years of age who presented with an ovarian neoplasm, in the study period of 7 years, 57% were the age group of 17-19 years, ovarian cystectomy was done in 17 (44%) patients, unilateral oophorectomy in 16 (41%) and salpingo-oophorectomy in 6 (15%). Histopathology reports showed that majority (88%) of the tumours were benign in nature, of which serous cystadenoma was the most common 14 (33%) and 3 (7%) malignant ovarian neoplasm. Radiological findings showed positive correlation with histopathology in the present study. Conclusions: Ovarian neoplasm in adolescent girls is rare but distressing, diagnosed on high index of suspicion. Early diagnosis and surgery are vital, aiming fertility preservation and female gonad preservation.